Analisis Tradisi Praktik Gadai Sawah Dalam Perspektif Fikih Muamalah Di Blok Babakan Palasah, Gantar, Indramayu - Mulyaningsih Mulyaningsih; Putri Hanifah Nur Islamiah; Wasiyah Wasiyah; Agus Rojak Samsudin (Gapenas Publisher, 2026)
This study examines the traditional practice of paddy field pawning (rahn) in Blok Babakan Palasah from the perspective of fiqh muamalah and qawa'id fiqhiyyah. The practice is commonly conducted through an oral agreement passed down through generations, in which the pledgee (murtahin) fully manages the pawned paddy field and enjoys its entire harvest during the pawning period, generally two to three years, without sharing the yield with the pledgor (rahin). Using a qualitative descriptive field research design with normative-juridical and sociological approaches, data were collected through interviews with pledgors, pledgees, and religious leaders, then analyzed using the interactive model of Miles, Huberman, and Saldana. The findings show that although the practice is regarded by most parties as a mutually beneficial and fair custom ('urf) rooted in social trust, it does not fully meet the requirements of a valid rahn contract because the pledgee's full appropriation of the harvest without compensation indicates riba and potential injustice toward the pledgor, as also confirmed by religious leaders. The study recommends restructuring the pawning agreement through separate contracts such as ijarah, mudharabah, or muzara'ah, accompanied by written documentation as a preventive measure against exploitative practices.